2013
DOI: 10.3168/jds.2012-5859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic type and casein haplotype on antioxidant activity of yogurts during storage

Abstract: The aim of this work was to investigate the antioxidant activity of yogurt made from the milk of 2 breeds-Italian Brown and Italian Holstein-characterized by different casein haplotypes (αS1-, β-, and κ-caseins) during storage up to 15 d. The casein haplotype was determined by isoelectric focusing; antioxidant activity of yogurt was measured using 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid). The statistical analysis showed a significant effect of the studied factors. Antioxidant activity increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 33 publications
5
37
0
1
Order By: Relevance
“…The antioxidant capacity is also conditioned by the heat treatment undergone by the milk for the manufacture of the yogurt (Galleher et al, 2005), by the fermentation and postacidification during storage that determine production of organic acids (Correia et al, 2004), and by possible aggregation of peptide processes that occur during the enzymatic hydrolysis of whey protein and CN (Adt et al, 2011). In a previous study, Perna et al (2013a) demonstrated that yogurts made from cow milk characterized by different CN haplotypes showed different antioxidant activity due to the specific amino acid sequence of the milk protein variants. Hernández-Ledesma et al (2005) showed that peptides released from the A variant of β-LG are small (3 kDa) and are mainly responsible for antioxidant activity compared with the AB variant of β-LG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant capacity is also conditioned by the heat treatment undergone by the milk for the manufacture of the yogurt (Galleher et al, 2005), by the fermentation and postacidification during storage that determine production of organic acids (Correia et al, 2004), and by possible aggregation of peptide processes that occur during the enzymatic hydrolysis of whey protein and CN (Adt et al, 2011). In a previous study, Perna et al (2013a) demonstrated that yogurts made from cow milk characterized by different CN haplotypes showed different antioxidant activity due to the specific amino acid sequence of the milk protein variants. Hernández-Ledesma et al (2005) showed that peptides released from the A variant of β-LG are small (3 kDa) and are mainly responsible for antioxidant activity compared with the AB variant of β-LG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antioxidant activity is strongly influenced by strain-specific characteristics of LAB (Kudoh et al, 2001;Ryhanen et al, 2001;Hernández-Ledesma et al, 2005;Virtanen et al, 2007;Gupta et al, 2009). In a recent report, Perna et al (2013a) observed that the antioxidant activity of yogurt made from cow milk was significantly influenced by the casein haplotype. This could be due to specific amino acid sequence of the milk protein variants.…”
Section: Introductionmentioning
confidence: 95%
“…Once absorbed in the small intestine bioactive peptides exert a beneficial effect on the various systems of the body such as the nervous system, the cardiovascular, endocrine, and immune systems (Erdmann et al 2008). Peptides exhibit various biological functions such as antimicrobial (Meira et al 2012), immunomodulatory (Qian et al 2011), antioxidant (Sabeena et al 2010, Perna et al 2013, antithrombic (Singh et al 2014), hypocholesterimic (Hartmann and Meisel 2007), and antihypertensive properties (Chen et al 2010, Phelan andKerins 2011). Soysauce, chungkokjang, natto, and kinema are involved in the process of enzymatic hydrolysis of protein, produce peptides and amino acids, which confer health benefits (Tamang and Nikkuni 1998).…”
Section: Bioproduction Of Peptidesmentioning
confidence: 99%
“…The antioxidant capacity of casein was determined by 2,2'-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) radical scavenging and ferric-reducing antioxidant power (FRAP) assays. The ABTS assay was determined according to the method of Re et al (1999), as modified by Perna et al (2013); FRAP assay was determined according to the method of Benzie and Strain (1996). Each determination and measurement was made in triplicate and the results for both assays were expressed as milligrams of Trolox equivalent (TE) per milligram of casein.…”
Section: Short Communicationmentioning
confidence: 99%
“…Before starting the test, approximately 250 animals in lactation were identified by isoelectric focusing to define their haplotypes (Perna et al, 2013). Haplotypes were formed by the combination of the individual allelic loci aggregated by α S1 -, β-, and κ-CN.…”
Section: Short Communicationmentioning
confidence: 99%